The representations of students about the school bullying - Korol, Natallia V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
This article emphasizes the importance of studying the phenomenon of bullying. The concept of bullying, cyberbullying, the forms of bullying, the theories of bullying and the consequences of bullying are considered. The results of the research of the Belarusian State University first year students’ views on the forms of school bullying, its consequences for the victim and ways of coping with the bullying are presented. Attention is drawn to the need of diagnostics and support of children, who have encountered bullying at school, within the psychological service in higher education in view of their propensity for depression, anxiety and low self-esteem.